Single crystal growth method, all-inorganic perovskite battery and preparation method of all-inorganic perovskite battery
The single crystal of methylammonium lead halide was grown by the constant temperature method and applied to all-inorganic perovskite solar cells, which solved the defects and complexity problems in the growth of perovskite single crystals and improved the humidity stability and performance of the battery.
Patent Information
- Application Number
- CN202411882525.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-11
AI Technical Summary
The existing perovskite single crystal growth methods have crystal defects and complex preparation process, and the humidity stability of all-inorganic perovskite solar cells is poor.
By controlling the components and temperature of the precursor solute, a single crystal of methylammonium lead halide was grown by the constant temperature method and applied to the preparation of all-inorganic perovskite solar cells.
The high-quality growth of perovskite single crystals is achieved, the humidity stability and battery performance of perovskite batteries are improved, and the long-term stability of the battery in a high-humidity environment is ensured.
Smart Images

Figure CN119800485A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of raw material preparation of perovskite cells, and in particular to a single crystal growth method, an all-inorganic perovskite cell and a preparation method thereof. Background Art
[0002] Perovskite materials have the characteristics of simple preparation and low cost, as well as their unique optoelectronic properties, which have attracted extensive attention from many researchers. Perovskite single crystal refers to a crystalline material composed of perovskite structural units, which has the characteristics of good symmetry, strong crystal stability, and excellent electrical and optical properties. It has a wide range of application potentials in the fields of photodetectors and light-emitting diodes.
[0003] Perovskite single crystals can be easily obtained using an inexpensive solution method. Currently, there are two synthetic methods to grow crystals: one is to lower the solution temperature to cause the crystal to precipitate at low temperature, and the other is a reverse temperature increase crystallization method. The perovskite single crystals grown by these two methods have crystal defects, and the preparation method is complicated. Whether it is the cooling or heating method to prepare single crystals, it is necessary to observe the crystal precipitation in time, and then adjust the temperature according to the size to make it continue to grow into a large-sized single crystal. In addition, the humidity stability of all-inorganic perovskite solar cells is poor. When the relative humidity is greater than 30%, the black phase of the film will quickly decompose in a short time, which is not conducive to the long-term stability of perovskite cells. Summary of the invention
[0004] In order to solve the defects in the prior art, the present invention provides a single crystal growth method, an all-inorganic perovskite battery and a preparation method thereof. The present invention grows a methylammonium lead halide single crystal by controlling the components and temperature of the precursor solute, and applies it to the preparation process of an all-inorganic perovskite solar cell. Due to the unique structural stability and Cl - Due to the crystallinity characteristics of the ion-regulated film, the finally prepared all-inorganic perovskite battery has strong humidity stability and excellent battery performance.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a single crystal growth method, comprising: dissolving methylamine halide and lead halide in a solvent, and then only heating at a constant temperature to obtain a methylammonium lead halide single crystal.
[0007] Preferably, the methylamine halide is selected from one or more of MAI, MACl, and MABr.
[0008] Preferably, the lead halide is selected from one or more of PbI2, PbCl2, and PbBr2.
[0009] Preferably, the methylamine halide is MAI, and the lead halide is PbCl2.
[0010] Preferably, the single crystal is selected from any one or more of MAPbCl3 single crystal, MAPbI3 single crystal, and MAPbBr3 single crystal.
[0011] Preferably, the single crystal is MAPbCl3 single crystal.
[0012] Preferably, the solvent is a mixed solvent of dimethylformamide and / or dimethyl sulfoxide.
[0013] Preferably, the solvent is dimethylformamide and dimethyl sulfoxide in a volume ratio of 1:1.
[0014] Preferably, the molar ratio of the methylamine halide to the lead halide is 1:(1-3).
[0015] Preferably, after dissolving the methylamine halide and the lead halide in the solvent, the concentration of the obtained mixed solution is 1-2M.
[0016] Preferably, the constant temperature heating temperature is 30-60°C.
[0017] In a second aspect, the present invention provides an all-inorganic perovskite battery, whose structure includes conductive glass, an electron transport layer, a perovskite light absorbing layer, a hole transport layer, and a metal electrode, wherein the raw material for preparing the perovskite light absorbing layer comprises the methylammonium lead halide single crystal obtained by the above-mentioned single crystal growth method.
[0018] The all-inorganic perovskite battery described in the present invention includes a planar heterojunction, a mesoporous structure, a formal structure, an inverted structure, and the like.
[0019] In a third aspect, the present invention provides a method for preparing an all-inorganic perovskite battery, comprising the following steps:
[0020] Cleaning conductive glass; preparing an electron transport layer; preparing a perovskite light-absorbing layer; preparing a hole transport layer; preparing a metal electrode; wherein the process of preparing the perovskite light-absorbing layer comprises: adding the methylammonium lead halide single crystal obtained by the above-mentioned single crystal growth method to a precursor solution, and then performing spin coating and annealing to obtain the result.
[0021] Preferably, the components of the precursor solution include any one or more of cesium iodide, lead iodide, and lead bromide.
[0022] Preferably, the preparation process of the electron transport layer comprises: depositing an ice-water mixture containing TiCl4 on the conductive glass, and drying the mixture.
[0023] The beneficial effects of the present invention are:
[0024] Temperature is one of the most important factors in the single crystal growth process, and temperature changes can affect the single crystal growth rate, crystal quality and structure. Under normal circumstances, as the temperature rises or decreases, the single crystal growth rate will accelerate, but too high a temperature will cause defects in the crystal and reduce the crystal quality. Moreover, whether it is by cooling or heating to promote crystal precipitation, the required time is relatively long, increasing the crystal growth cycle, and if the components of the solution are too many, the impurities present will inevitably affect the purity of the single crystal, and therefore, the factors affecting crystal growth are more complicated. The present invention changes the usual cooling precipitation or heating precipitation, but adopts a constant temperature method to make the crystal grow, only needs to set a fixed temperature in the initial stage, and does not need to repeatedly adjust the temperature during the entire growth cycle, and this method is simple and easy to operate. The single crystal grown by this method has good crystallinity and preferential orientation growth, and will not change the light absorption cutoff edge of the perovskite film, and by this method, most seed crystals will be integrated into a large single crystal, increasing the size of the single crystal to a greater extent.
[0025] The obtained methylammonium lead halide single crystal is applied in the preparation process of all-inorganic perovskite cells. Due to the unique structural stability of the single crystal and the characteristics of halide ions regulating the crystallinity of the film, it is not necessary to introduce other organic chlorides to passivate the grain boundaries of the perovskite film and improve the film morphology. In addition, the present invention introduces an appropriate amount of single crystals into the perovskite cell, which is equivalent to introducing additional carriers, thereby improving the photoelectric performance of the material, and improving the humidity stability of the perovskite solar cell. The final prepared perovskite cell still maintains an initial efficiency of 90% after being placed in the air for 30 days, which provides a new idea for the commercial application of perovskite cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a flow chart of single crystal preparation of the present invention;
[0027] Figure 2 This is a morphology image of the single crystals prepared by sequence number 1 and sequence number 2 in Example 1;
[0028] Figure 3 The XRD diagram of the single crystals prepared by sequence number 1 and sequence number 2 in Example 1;
[0029] Figure 4 The UV-visible absorption spectra of the all-inorganic perovskite cells prepared in Example 2 and Comparative Example 1;
[0030] Figure 5 This is a stability test diagram of the all-inorganic perovskite battery prepared in Example 2 and Comparative Example 1 placed under a relative humidity of 30% for 30 days;
[0031] Figure 6 SEM images of the perovskite films prepared in Comparative Example 1 and Example 2. DETAILED DESCRIPTION
[0032] In order to enable those skilled in the art to better understand the technical solution of the invention, the present invention is further described in detail below in conjunction with specific implementation methods.
[0033] Example 1: Study on Single Crystal Growth Method
[0034] The single crystal preparation process of this embodiment is shown in Figure 1 , the steps are as follows:
[0035] According to a certain molar ratio (1:1, 1:2, 1:3), appropriate amounts of methylamine halide and lead halide are weighed, and then they are dissolved in a mixed solvent of dimethylformamide and dimethyl sulfoxide (DMF and DMSO) with a volume ratio of 1:1, and mixed to obtain a mixed solution (concentration of 1M, 1.5M, 2M); stirred at room temperature until the mixed solution is clear and has no precipitation, and then filtered into a vial sealed with a sealing film through a polytetrafluoroethylene with a pore size of 0.22μm, and the vial is placed in an oil bath pot and heated at a constant temperature (30℃, 50℃, 60℃) to promote crystal growth. No parameters need to be changed during this process, including temperature or solution volume; after observation, crystals are precipitated after being placed for 2 hours, and then the crystals gradually increase. Finally, the single crystal is taken out, the surface is cleaned with anhydrous ether, and it is placed in a dry environment for drying. The component ratio and temperature conditions of the raw materials in the preparation process are shown in Table 1.
[0036] Table 1
[0037]
[0038]
[0039] The morphology of the prepared single crystal is as follows Figure 2 As shown, the MAPbCl3 single crystal prepared by No. 1 is transparent and colorless, with an irregular square size of 3mm, and many seed crystals are stacked together to form a larger single crystal size of about 1cm; while the single crystal grown by No. 2 is needle-shaped, although many crystals are precipitated, all of them are very small. Due to excessive raw material dosage, No. 3 and No. 4 will find a large amount of powder precipitation during the initial stirring and dissolving process, and single crystals cannot be grown; No. 5 and No. 6 can be partially dissolved due to the high concentration of the mixed solution, but it leads to oversaturation, so single crystals cannot be precipitated; For temperature regulation, try to observe the single crystal precipitation phenomenon of No. 7 and No. 8 under the same raw material molar ratio and mixed solution concentration. It is found that the temperature exceeds 30°C, and the crystal cannot be precipitated, and the culture dish is still a transparent and clear yellow solution.
[0040] XRD is used to determine the crystal orientation and purity, such as Figure 3As shown in the figure, the single crystal grown under the No. 1 environment can be observed to have sharp diffraction peaks at 2θ=15.75°, 31.55°, and 48.05°, representing the (100), (200), and (300) crystal planes, respectively. The grown single crystal has better orientation and better quality. The diffraction peak of the (210) crystal plane of the single crystal grown under the No. 2 environment is sharper, and the intensity of the (100) and (200) diffraction peaks is weaker than that of No. 1, indicating that the purity and orientation preference of the perovskite single crystal grown under this environment are relatively poor.
[0041] By exploring the conditions for growing single crystals in Example 1, it was found that the product obtained by using methylamine iodide (MAI) and lead chloride (PbCl2) as solutes has better crystallinity. Therefore, the single crystal grown by sequence number 1 was used in an all-inorganic perovskite solar cell to explore whether it can play a role in improving stability.
[0042] Since the present invention applies MAPbCl3 single crystal to inorganic perovskite cells, and MA in MAPbCl3 is an organic molecule, a small amount of introduction can adjust the crystallization and performance of the film. MA materials will volatilize during high-temperature annealing, and if too much is introduced, it will lead to incomplete volatilization, and some organic materials will remain in the film, changing the properties of the all-inorganic perovskite cell. In addition, too much Cl is introduced into the precursor solution. - The absorption cutoff edge and optical band gap of the perovskite film will change. Therefore, the present invention strives to select the addition amount of MAPbCl3 single crystal to be 5 mg / ml without changing the properties and band gap of the all-inorganic perovskite cell, and compares the samples without adding and adding 5 mg / ml MAPbCl3 single crystal to analyze the effect of the single crystal of the present invention on the photovoltaic performance of the perovskite. The specific preparation process is shown in Example 2 and Comparative Example 1.
[0043] Example 2 Preparation of all-inorganic perovskite battery
[0044] This embodiment provides a formal all-inorganic perovskite solar cell, whose structure includes conductive glass, electron transport layer, perovskite light absorption layer, hole transport layer, and metal electrode from bottom to top.
[0045] The preparation method of the formal all-inorganic perovskite battery includes the following steps:
[0046] (1) Cleaning of conductive glass: The indium tin oxide (ITO) conductive glass substrate is first gently wiped clean with anhydrous ethanol, then placed in a mixed solution of glass cleaner and ultrapure water for 30 minutes under ultrasonic treatment. After drying, the ITO is placed in a UV light and ozone cleaning machine for 10 minutes to remove impurities on the substrate surface and improve the substrate wettability.
[0047] (2) Preparation of electron transport layer: 4.5 ml of TiCl4 solution was added dropwise onto 200 ml of ice frozen by ultrapure water, and the ice was allowed to melt naturally at room temperature to form an ice-water mixed solution; then, clean glass was neatly arranged on dust-free paper, and yellow tape was used to stick along the upper edge of the conductive surface of the ITO glass and placed in a culture dish with the conductive surface facing up, and treated with a UV ozone machine for 10 min; after the ice melted into a thin layer, it was poured into a culture dish containing ITO conductive glass, and the ITO glass substrate was immersed in 40 mM TiCl4 aqueous solution. Finally, after reacting in a 70°C drying oven for 60 min, a dense TiO2 electron transport layer with a thickness of about 50 nm was formed; the use of this electron transport layer will make the energy level more matched, which is conducive to carrier transport and extraction.
[0048] (3) Preparation of perovskite light absorbing layer: The precursor solution was prepared by dissolving 207.68 mg of cesium iodide (CsI), 461.5 mg of lead iodide (PbI2), 73.45 mg of lead bromide (PbBr2) and 5 mg of methylammonium lead chloride (MAPbCl3) single crystals in 1 mL of DFM:DMSO (volume ratio of 4:2) solvent, stirring for 1 hour to fully dissolve the resulting light yellow clear liquid, which was then spin-coated on the electron transport layer by two-step spin coating. , the spin coating amount was 50 μL, and the two-step speed parameters were 1000 rpm for 10 s, acceleration of 100 rpm / s, and 4000 rpm for 30 s, acceleration of 1000 rpm / s, and 200 μL of chlorobenzene was added as an anti-solvent in the last 15 s of the spin coating time to promote the crystallization of the perovskite film. Finally, the spin-coated film was placed on a hot stage at 180°C for thermal annealing for 10 min to obtain a perovskite light-absorbing layer;
[0049] (4) Preparation of hole transport layer: First, the prepared perovskite film was removed from the heating table and placed on the table to cool. Then, 40 μl of Spiro-OMeTAD solution (the solvent is chlorobenzene) was taken and the spin coating speed was 1500 rpm for 30 s. The acceleration was 1500 rpm / s. The solution was evenly spread on the surface of the black perovskite light-absorbing layer to obtain a hole transport layer. Subsequently, the spin-coated film was stored away from light for more than 8 hours to ensure that it was fully oxidized.
[0050] (5) Preparation of metal electrode: Au electrode was deposited onto the hole transport layer by thermal evaporation method to form an electrode with a thickness of 80 nm.
[0051] Comparative Example 1 Preparation of all-inorganic perovskite battery
[0052] The same as Example 2, except that in step (3), 5 mg of methylammonium lead chloride (MAPbCl3) single crystal was not added.
[0053] The UV-visible absorption spectra of the all-inorganic perovskite cells prepared in Example 2 and Comparative Example 1 are shown in Figure 4 . Figure 4 It can be clearly observed that after the introduction of 5 mg / ml MAPbCl3 in Example 2, the absorption intensity in the wavelength range of 500-600 nm is improved, but the absorption cutoff edge is 722 nm, indicating that the corresponding band gap has not changed. It also shows that the present invention can improve the absorption performance of the perovskite film without changing the band gap.
[0054] The all-inorganic perovskite cells prepared in Example 2 and Comparative Example 1 were placed under a relative humidity of 30% for 30 days for stability testing. Figure 5 It can be seen that the sample after the introduction of single crystal can still maintain the initial efficiency of 90% under humidity conditions for 30 days, while the sample without the introduction of single crystal has a significant decrease in battery efficiency.
[0055] The perovskite films prepared in Comparative Example 1 and Example 2 were characterized by SEM morphology. Figure 6 It can be found that after the MAPbCl3 single crystal is introduced into the present invention, the grain boundary of the perovskite film can be passivated and the film morphology can be improved without introducing other organic chlorides.
[0056] The above are only preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be regarded as limiting the present invention, and the protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A single crystal growth method, characterized in that: include: After dissolving methylamine halide and lead halide in a solvent, the mixture is simply heated at a constant temperature to obtain a methylammonium lead halide single crystal.
2. The single crystal growth method according to claim 1, characterized in that: The methylamine halide is selected from one or more of MAI, MACl and MABr.
3. The single crystal growth method according to claim 1, characterized in that: The lead halide is selected from one or more of PbI2, PbCl2, and PbBr2.
4. The single crystal growth method according to claim 1, characterized in that: The methylammonium lead halide single crystal is selected from any one or more of MAPbCl3 single crystal, MAPbI3 single crystal, and MAPbBr3 single crystal.
5. The single crystal growth method according to any one of claims 1 to 4, characterized in that: The molar ratio of the methylamine halide to the lead halide is 1:(1-3).
6. The single crystal growth method according to any one of claims 1 to 4, characterized in that: After the methylamine halide and the lead halide are dissolved in the solvent, the concentration of the obtained mixed solution is 1-2M.
7. The single crystal growth method according to any one of claims 1 to 4, characterized in that: The constant temperature heating temperature is 30-60°C.
8. An all-inorganic perovskite battery, characterized in that: Its structure includes conductive glass, an electron transport layer, a perovskite light absorbing layer, a hole transport layer, and a metal electrode, wherein the raw material for preparing the perovskite light absorbing layer comprises a methylammonium lead halide single crystal obtained by the single crystal growth method according to any one of claims 1 to 7.
9. A method for preparing an all-inorganic perovskite battery, characterized in that: The following steps are involved: Cleaning conductive glass; preparing an electron transport layer; preparing a perovskite light absorbing layer; preparing a hole transport layer; Preparation of metal electrodes; wherein the process of preparing the perovskite light-absorbing layer comprises: adding the methylammonium lead halide single crystal obtained by the single crystal growth method according to any one of claims 1 to 7 to a precursor solution, and then performing spin coating and annealing to obtain the result.
10. The method for preparing an all-inorganic perovskite battery according to claim 9, characterized in that: The preparation process of the electron transport layer comprises: depositing an ice-water mixture containing TiCl4 on the conductive glass, and drying the mixture.